2013
DOI: 10.1158/0008-5472.can-13-0069
|View full text |Cite|
|
Sign up to set email alerts
|

EPR Oxygen Images Predict Tumor Control by a 50% Tumor Control Radiation Dose

Abstract: Clinical trials to ameliorate hypoxia as a strategy to relieve the radiation resistance it causes have prompted a need to assay the precise extent and location of hypoxia in tumors. Electron Paramagnetic Resonance oxygen imaging (EPR O2 imaging) provides a non-invasive means to address this need. To obtain a preclinical proof of principle that EPR O2 images could predict radiation control, we treated mouse tumors at or near doses required to achieve 50 percent control (TCD50). Mice with FSa fibrosarcoma or MCa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…Based on survival data, HP 10 was most strongly correlated with curative treatment (pseudo-R 2 = 0.59) and identifying tumors at risk for treatment failure, consistent with clinical data obtained from oxygen-sensitive electrodes. In a follow-up radiation treatment study, HP 10 > 10% and HP 10 > 15% were predictive for treatment failure in FSa tumors and MCa4 (mammary carcinoma) tumors, respectively (81). The hypoxic treatment outcomes cut-offs observed in this study are similar to hypoxic cut-offs observed in human patients.…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiasupporting
confidence: 68%
“…Based on survival data, HP 10 was most strongly correlated with curative treatment (pseudo-R 2 = 0.59) and identifying tumors at risk for treatment failure, consistent with clinical data obtained from oxygen-sensitive electrodes. In a follow-up radiation treatment study, HP 10 > 10% and HP 10 > 15% were predictive for treatment failure in FSa tumors and MCa4 (mammary carcinoma) tumors, respectively (81). The hypoxic treatment outcomes cut-offs observed in this study are similar to hypoxic cut-offs observed in human patients.…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiasupporting
confidence: 68%
“…of Brussels, have embarked on studies to localize areas for eventual surgical removal or correction of regions that have reduced oxygen tension due to tumors, or as a calibration of oxygen pressures suitable for subsequent radiation therapy that has also been a major thrust in the Univ. of Chicago group as well, who are experts on radiation treatment of tumors and tissue [28,29,42].…”
Section: In-vivo Instrumentation With Human Subjectsmentioning
confidence: 99%
“…It is known that tumors treated to a uniform 50% tumor control dose (TCD 50 ) exhibit different control probability depending on their oxygenation (Fig. 1) [2]. Hypoxia desensitizes tumors to radiation and mandate higher treatment doses.…”
Section: Introductionmentioning
confidence: 99%